2017
DOI: 10.1097/mpg.0000000000001444
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Erythrocyte Sedimentation Rate and C‐Reactive Protein With Pediatric Inflammatory Bowel Disease Activity

Abstract: We aimed to examine correlation of erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) with diagnosis of inflammatory bowel disease and with clinical, endoscopic, histological, and radiographic disease activity during follow-up. We reviewed charts of 135 children with inflammatory bowel disease and correlated their ESR and CRP values with disease activity in various encounters during 5 years. Normal ESR and CRP values were observed in up to 28% of children with Crohn disease and 42% of children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 10 publications
6
21
0
2
Order By: Relevance
“…A post hoc analysis of a prospective clinical trial showed that CRP levels failed to discriminate between patients in clinical remission, with endoscopic inflammation and with mucosal healing (88). In pediatric patients with UC, neither marker was found to be useful in predicting clinical, endoscopic, or histological UC disease activity (89).…”
Section: Resultsmentioning
confidence: 99%
“…A post hoc analysis of a prospective clinical trial showed that CRP levels failed to discriminate between patients in clinical remission, with endoscopic inflammation and with mucosal healing (88). In pediatric patients with UC, neither marker was found to be useful in predicting clinical, endoscopic, or histological UC disease activity (89).…”
Section: Resultsmentioning
confidence: 99%
“…CRP became normal first. The mean time was 22 days, which was less than half the time for ESR to become normal (59 days), since CRP correlated with clinical activity while ESR correlated well with endoscopic and histologic colitis [45]. Growing evidence has shown that increased platelets counts seemed to play a crucial role in determining the hypercoagulable state observed in CD [46].…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistency in the inflammatory markers' response to inflammation and their lack of accuracy have been reported frequently. 63,64 Similar to saccharin, 4-dodecyl benzene sulfonic acid was positively associated with ESR but negatively associated with CRP. It was also positively correlated with calprotectin and the WBC count.…”
Section: Negative-ion Modementioning
confidence: 99%